(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
Echoing historical interpretations that reveal how human mobility entails gradual transition from “Europeanness” to non-European worlds, the chapters in Part I analyze shifting symbolic constructions of “Europe” and their imprints on human materiality and landscapes. Anlam Filiz and Oksana Ermolaeva position themselves at opposing geographic standpoints, at the margins of Europe’s Southern and Northern borders, thus contributing to the building of multiple and contested conceptualizations of European liminal, transitory spaces.